2010
DOI: 10.1073/pnas.1009076107
|View full text |Cite
|
Sign up to set email alerts
|

Neural activity associated with monitoring the oscillating threat value of a tarantula

Abstract: Phylogenetic threats such as spiders evoke our deepest primitive fears. When close or looming, such threats engage evolutionarily conserved monitoring systems and defense reactions that promote self-preservation. With the use of a modified behavioral approach task within functional MRI, we show that, as a tarantula was placed closer to a subject's foot, increased experiences of fear coincided with augmented activity in a cascade of fear-related brain networks including the periaqueductal gray, amygdala, and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

37
302
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(342 citation statements)
references
References 38 publications
37
302
2
1
Order By: Relevance
“…The present investigation examined the hypothesis that an attachment figure may act as a safety signal during a threatening experience, relying on neural regions known to be involved in signaling safety and reducing distress or threat. Consistent with this analysis, we found that viewing an attachment figure (romantic partner) during an experience of physical pain led to greater activity in the VMPFC, a region implicated in safety signaling and fear extinction (10)(11)(12)(13)(14)(15)(16), and attenuated reports of pain and pain-related neural activity. Specifically, we found that viewing partner pictures while receiving pain led to lower pain ratings than viewing control pictures while receiving pain, particularly during the high-pain trials.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The present investigation examined the hypothesis that an attachment figure may act as a safety signal during a threatening experience, relying on neural regions known to be involved in signaling safety and reducing distress or threat. Consistent with this analysis, we found that viewing an attachment figure (romantic partner) during an experience of physical pain led to greater activity in the VMPFC, a region implicated in safety signaling and fear extinction (10)(11)(12)(13)(14)(15)(16), and attenuated reports of pain and pain-related neural activity. Specifically, we found that viewing partner pictures while receiving pain led to lower pain ratings than viewing control pictures while receiving pain, particularly during the high-pain trials.…”
Section: Discussionsupporting
confidence: 70%
“…Thus, in rats, stimulating the VMPFC while presenting a fearinducing cue diminishes fear responding, suggesting a role for this region in inhibiting the fear response (18). Similarly, in humans, increased activity in the VMPFC (including the subgenual anterior cingulate cortex; subACC) has been observed in response to safety signals (relative to fear-predictive stimuli) (11)(12)(13)(14), and greater activity in the VMPFC/subACC during fear extinction or learned safety has been associated with reduced fear responding (reductions in skin conductance) (14). Thus, in the context of fear learning, VMPFC activity appears to track stimuli that signal safety, and this activity is thought to modulate other neural regions that are involved in responding to the threat at hand.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In short, they have shown that distant or potential threats are associated with activity in the ventromedial prefrontal cortex (vmPFC), but as the threat becomes nearer and intense, brain activity shifts to the PAG [13][14][15]. In these experiments, actual threat situations were used.…”
Section: Introductionmentioning
confidence: 99%